Stochastic and Balanced Distributed Energy-Efficient Clustering (SBDEEC) for Heterogeneous Wireless Sensor Networks - Brahim, Elbhuru; Rachid, Saadane; Zamora, Alba-Pagès; Aboutajdine, Driss (INFOCOMP Journal of Computer Science, 2009)
Typically, a wireless sensor network contains an important number of inexpensive power constrained sensors which collect data from the environment and transmit them towards the base station in a cooperative way. Saving energy and therefore, extending the wireless sensor networks lifetime, imposes a great challenge. Many new protocols are specifically designed for these raisons where energy awareness is an essential consideration. The clustering techniques are largely used for these purposes. In this paper, we present and evaluate a Stochastic and Balanced Developed Distributed Energy-Efficient Clustering (SBDEEC) scheme for heterogeneous wireless sensor networks. This protocol is based on dividing the network into dynamic clusters. The cluster’s nodes communicate with an elected node called cluster head, and then the cluster heads communicate the information to the base station. SBDEEC introduces a balanced and dynamic method where the cluster head election probability is more efficient. Moreover, it uses a stochastic scheme detection to extend the network lifetime. Simulation results show that our protocol performs better than the Stable Election Protocol (SEP) and than the Distributed EnergyEfficient Clustering (DEEC) in terms of network lifetime. In the proposed protocol the first node death occurs over 90% times longer than the first node death in DEEC protocol and by about 130% than SEP.